Data Maning Techniques and Business Intelligence Tools for Barriers to Entry Analysis and Management - Mach, Maria Antonina (Wydawnictwo Uniwersytetu Ekonomicznego we Wrocławiu, 2008)
Barriers to entry are considered an important feature in enterprise’s everyday strategy. This is because they may enable or disable to gain a competitive advantage over other participants in the market. Moreover, they may give an enterprise a strong market position, if they are properly built. Because barriers to entry are so important, and because they change in time (as many other elements of the economic environment) it seems justified to use computer tools in the process of managing barriers to entry. In the paper some advantages of data mining and Business Intelligence systems used for barriers to entry management are pointed out.
Prace Naukowe Uniwersytetu Ekonomicznego we Wrocławiu = Research Papers of Wrocław University of Economics; 2008; Nr 25, s. 94-104